Let ​f(x)equalsx squared minus 3 x and ​g(x)equals7 plus x. Find the following.

​(a) left parenthesis f plus g right parenthesis left parenthesis x right parenthesis
​(b) left parenthesis f minus g right parenthesis left parenthesis x right parenthesis
​(c) left parenthesis f times g right parenthesis left parenthesis x right parenthesis
​(d) left parenthesis StartFraction f Over g EndFraction right parenthesis
​(x)
​(e) The domain of StartFraction f Over g EndFraction
Question content area bottom
Part 1
​(a) left parenthesis f plus g right parenthesis left parenthesis x right parenthesisequals
  
enter your response here ​(Simplify your answer. Do not​ factor.)

1 answer

To solve the problem, we need to find various operations involving the functions \( f(x) \) and \( g(x) \).

Given:

  • \( f(x) = x^2 - 3x \)
  • \( g(x) = 7 + x \)

Let's compute each part:

(a) \( (f + g)(x) \)

To find \( (f + g)(x) \), we add the two functions:

\[ (f + g)(x) = f(x) + g(x) \]

Substituting in the expressions for \( f(x) \) and \( g(x) \):

\[ (f + g)(x) = (x^2 - 3x) + (7 + x) \]

Now, combine like terms:

\[ = x^2 - 3x + 7 + x \] \[ = x^2 - 2x + 7 \]

Thus,

\[ \boxed{x^2 - 2x + 7} \]

(b) \( (f - g)(x) \)

To find \( (f - g)(x) \), we subtract \( g(x) \) from \( f(x) \):

\[ (f - g)(x) = f(x) - g(x) \]

Substituting the expressions:

\[ (f - g)(x) = (x^2 - 3x) - (7 + x) \]

Distributing the negative sign:

\[ = x^2 - 3x - 7 - x \]

Combining like terms:

\[ = x^2 - 4x - 7 \]

Thus,

\[ \boxed{x^2 - 4x - 7} \]

(c) \( (f \times g)(x) \)

To find \( (f \times g)(x) \), we multiply the two functions:

\[ (f \times g)(x) = f(x) \cdot g(x) \]

Substituting the expressions:

\[ (f \times g)(x) = (x^2 - 3x)(7 + x) \]

Using the distributive property:

\[ = x^2 \cdot (7 + x) - 3x \cdot (7 + x) \] \[ = 7x^2 + x^3 - 21x - 3x^2 \] \[ = x^3 + 4x^2 - 21x \]

Thus,

\[ \boxed{x^3 + 4x^2 - 21x} \]

(d) \( \left(\frac{f}{g}\right)(x) \)

To find \( \left(\frac{f}{g}\right)(x) \), we divide \( f(x) \) by \( g(x) \):

\[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} \]

Substituting the expressions:

\[ \left(\frac{f}{g}\right)(x) = \frac{x^2 - 3x}{7 + x} \]

Thus,

\[ \boxed{\frac{x^2 - 3x}{7 + x}} \]

(e) The domain of \( \left(\frac{f}{g}\right) \)

The domain of \( \left(\frac{f}{g}\right)(x) \) is determined by the values of \( x \) for which \( g(x) \) is not equal to zero:

\[ g(x) = 7 + x \neq 0 \implies x \neq -7 \]

Therefore, the domain of \( \left(\frac{f}{g}\right)(x) \) in interval notation is:

\[ \boxed{(-\infty, -7) \cup (-7, \infty)} \]